Evaluation of Two "in vitro" Digestibility Tests with the "in vivo" Test of Alfalfa (Medicago sativa) in Guinea Pig (Cavia porcellus) Feeding - S., López; H., Guevara; N., Duchi; G., Moreno (European Scientific Journal, ESJ, 2018)
The purpose of the present study was to compare two types of "in vitro" digestibility assays by using commercial enzymes and guinea pig cecalliquor with the in vivo assay, to identify the assay that most resembles the in vivo response. The alfalfa was used in two cutting times of 30 and 45 days. The "in vivo" digestibility of alfalfa was analyzed, obtaining that after 30 days of cutting the digestibility was 53.64% and at 45 days it was 47.72%, while for the digestibility "in vitro", the DaisyIIÂ®-Ankom Technology with cecal liquor and commercial pepsin; for the cecal liquor a value of 55.46% and 49.90% was obtained, for the alfalfa in the two cutting times, while the digestibility with enzymes was 71.01% and 66.34% respectively. It was determined that the method with more relation to the in vivo test corresponds to the trial with cecal liquor, because it presents a lower statistical difference (p <0.05) for both cut-off times. At the same time, it is identified that the protein is the nutrient that has a higher digestibility coefficient, becoming an indicator of the nutritional quality of the food.